2022
DOI: 10.1007/s00406-022-01440-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Research Domain Criteria using a transdiagnostic mini-RDoC assessment in mental disorders: a confirmatory factor analysis

Abstract: This study aimed to build on the relationship of well-established self-report and behavioral assessments to the latent constructs positive (PVS) and negative valence systems (NVS), cognitive systems (CS), and social processes (SP) of the Research Domain Criteria (RDoC) framework in a large transnosological population which cuts across DSM/ICD-10 disorder criteria categories. One thousand four hundred and thirty one participants (42.1% suffering from anxiety/fear-related, 18.2% from depressive, 7.9% from schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Likewise focusing on self-report and behavioral units. Förstner et al (2022) found a structure of four latent and transnosological factors (PVS, NVS, CS, and SP) using a confirmatory factor analysis (CFA) approach, although these factors were not cross-modal. Differential associations between PV and NV symptom scores and clinical impairment, antidepressant response, and inflammation-related immunomarkers were revealed in a sample of MDD patients by Medeiros et al (2020).…”
Section: Cross-domain Positive and Negative Valence Systemsmentioning
confidence: 99%
“…Likewise focusing on self-report and behavioral units. Förstner et al (2022) found a structure of four latent and transnosological factors (PVS, NVS, CS, and SP) using a confirmatory factor analysis (CFA) approach, although these factors were not cross-modal. Differential associations between PV and NV symptom scores and clinical impairment, antidepressant response, and inflammation-related immunomarkers were revealed in a sample of MDD patients by Medeiros et al (2020).…”
Section: Cross-domain Positive and Negative Valence Systemsmentioning
confidence: 99%
“…This investigation is an observational cross-sectional study assessing four core domains of the RDoC matrix (PVS, NVS, CS, and SP) within the German research network for mental disorders [Forschungszentrum zu psychischen Erkrankungen; FZPE] (46) as outlined by Förstner et al (12). Study centers throughout the FZPE network recruited participants for clinical and observational studies.…”
Section: Participantsmentioning
confidence: 99%
“…The RDoC approach views mental disorders as syndromes at multiple levels, also connected to disrupted or dysfunctional brain circuitry (6,7). To gain a better understanding of the links between disease-specific symptomatology and the underlying neural mechanisms of emotional (dys) function, the latent RDoC domains Positive (PVS) and Negative Valance System (NVS), Cognitive Systems (CS) and Social Processes (SP) were established and proved to be valid research constructs (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neural synchronization reflects the extent to which voxel-specific neural activity correlates between individuals. A high degree of synchronization suggests a population-wide similarity in the neural response to a common stimulus and may provide the basis by which we share an understanding of the world with other people that is necessary for many key high-level social functions ( Zaki and Ochsner, 2009 ; Adolphs et al. , 2016 ; Hasson and Frith, 2016 ; Nummenmaa et al.…”
mentioning
confidence: 99%